Двухволновой сенсор дистанционной селекции естественных поверхностей - Ivanchenko, I. A.; Budijanskaja, L. M.; Vaksman, Yu. F. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
A sensor based on the active two-wave method of recognizing natural surfaces has been developed. The proposed method simplifies the determination of the reflective properties of a surface and reduces the error of range measurements. A block diagram of the sensor is presented, and its operating algorithm is described. The remote characteristics of the sensor are provided.